Foundations of physical education, exercise science, and sport - Walton-Fisette, Jennifer L.; Wuest, Deborah A. (New York, NY McGraw Hill, 2024)
The twenty-first edition of Foundations of physical education, exercise science, and sport continues its dual emphasis on providing students with an overview of disciplinary knowledge and encouraging them to explore the expanding career opportunities. This edition reflects the dynamic nature of the field today and is designed for use in introductory and foundations courses. Specifically, the most significant change in this edition is an explicit emphasis placed on social justice, diversity, and cultural humility. These concepts and issues have been a component of the text for some time; however we have created social justice boxes in each chapter to highlight the salient social issues that are concerning and prevalent related to the chapter focus
1. Meaning and scope -- 2. Philosophy, goals, and objectives -- 3. Health and physical activity in our society -- 4. Historical foundations -- 5. Motor behavior -- 6. Biomechanical foundations -- 7. Exercise physiology and fitness -- 8. Sociological foundations -- 9. Sport and physical activity psychology -- 10. Physical education pedagogy -- 11. Career and professional development -- 12. Teaching and coaching careers -- 13. Fitness- and heath-related careers -- 14. Sport management, media and sport related careers -- 15. Future professional as leaders and advocates
"This International Student Edition is for use outside of the U.S." -- book cover
Includes bibliographical references and index
Keywords: Physical education and training; Sports; Physical education and training -- Vocational guidance; Sports -- Vocational guidance